Планування рекламної кампанії сучасного підприємства - Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна; Arestenko, Tetiana (My University, 2018)
UK: У роботі досліджено основні підходи до планування рекламної діяльності сучасних підприємств, розглянуто основні методики та виявлено відмінності, які полягають у визначенні послідовності етапів планування та їх функціональному наповненні. Опрацьовано пропозиції щодо практичного впровадження визначених методик з урахуванням фінансових можливостей підприємств та економічної доцільності конкретних рекламних заходів. EN: Basic advertising tools for planning managing of advertising campaign are cover in the paper. Differences of main structure types of campaign which founded on determination of the sequence of planning stages and their functional filling. Proposals on the practical implementation of certain methods with consideration of finan-cial possibilities of enterprises and economic expediency of concrete advertising measures are done in the paper. Of great importance when planning an advertising campaign is the spatial coverage, the capacity of the market, which operates the company, as well as the quality of the proposed goods. An advertiser also needs to optimize the se-lection of media on the basis of characteristics such as the cost of advertising space, target audience, intensity and fre-quency of possible contacts.
Planning advertising campaign of modern enterprise
Keywords: реклама; планування рекламної кампанії; носії реклами; бюджет реклами; ефективність реклами; advertisement; planning advertising campaign; promotional media; advertising content; budget of advertising; effectiveness of advertising